2021
DOI: 10.1111/ijac.13656
|View full text |Cite
|
Sign up to set email alerts
|

Properties of TiN–Al2O3–TiCN–TiN, TiAlN, and DLC‐coated Ti(C,N)‐based cermets and their wear behaviors during dry cutting of 7075 aluminum alloys

Abstract: Ti(C,N)-based cermets have been used as cutting tools due to their excellent hardness, phase stability, and wear resistance. These properties make the cermets possible for high-temperature machining. 1 In addition, Ti(C,N)-based cermets show higher hardness, lower friction coefficient compared with the cemented carbide, superior toughness than the ceramics, and more cost-effective than the PCBN. Ti(C,N)-cermet cutting tools are now mainly used for semifinishing and finishing and high-speed cutting of stainless… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 36 publications
0
6
0
Order By: Relevance
“…Both abrasives and adhesives suffer from continuous wear during grinding, so a balance should be struck between the abrasives and adhesives. The larger the surface area of the abrasive tip is, the more grinding heat and cutting force will be applied 36–38 . The local high temperature in the contact area will lead to the softening of rail materials, and the smaller debris will also be heated into sphericity.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Both abrasives and adhesives suffer from continuous wear during grinding, so a balance should be struck between the abrasives and adhesives. The larger the surface area of the abrasive tip is, the more grinding heat and cutting force will be applied 36–38 . The local high temperature in the contact area will lead to the softening of rail materials, and the smaller debris will also be heated into sphericity.…”
Section: Resultsmentioning
confidence: 99%
“…The larger the surface area of the abrasive tip is, the more grinding heat and cutting force will be applied. [36][37][38] The local high temperature in the contact area will lead to the softening of rail materials, and the smaller debris will also be heated into sphericity. As a result of the ploughing of the blunt abrasive, the rail surface is grooved, the surface roughness is higher, the coefficient of friction is lower, and the matrix adhesive remains on the rail surface.…”
Section: Interface Formation and Wear Mechanism Of Cermetmentioning
confidence: 99%
“…This type of cutting insert has good thermal stability, high mechanical stability, high impact resistance, and suitable for finish cutting conditions. This material is used commonly to make cutting tools in machining in general and in gear machining in particular [36]. Each experiment used sixteen new cutting inserts to attach to cutting head.…”
Section: Experimental Processmentioning
confidence: 99%
“…The authors report that the incorporation of AlO X N Y into the protective coatings enhanced the bio-corrosion resistance of Mg in simulated physiological environments . Liu et al reported the enhanced tribological behavior of Al7075 when coated with TiAlN via PVD . Noder et al published their findings reporting the improved tribological behavior of PVD-coated Al alloys machined for automotive structural components .…”
Section: Introductionmentioning
confidence: 99%
“…2 Liu et al reported the enhanced tribological behavior of Al7075 when coated with TiAlN via PVD. 3 Noder et al published their findings reporting the improved tribological behavior of PVD-coated Al alloys machined for automotive structural components. 4 Ishizaki et al reported the use of CVD to protect Mg alloys (AZ321) from corrosion by inducing superhydrophobic characteristics to the surface.…”
Section: ■ Introductionmentioning
confidence: 99%